Biomaterial‐Stabilized Soft Tissue Healing for Healing of Critical‐Sized Bone Defects: the Masquelet Technique. Issue 6 (8th February 2016) - Tarchala, Magdalena; Harvey, Edward J.; Barralet, Jake
Abstract : Critical‐sized bone defects present a significant burden to the medical community due to their challenging treatment. However, a successful limb‐salvaging technique, the Masquelet Technique (MT), has significantly improved the prognosis of many segmental bone defects in helping to restore form and function. Although the Masquelet Technique has proven to be clinically effective, the physiology of the healing it induces is not well understood. Multiple modifiable factors have been implicated by various surgical and research teams, but no single factor has been proven to be critical to the success of the Masquelet Technique. In this review the most recent clinical and experimental evidence that supports and helps to decipher the traditional Masquelet, as well as the modifiable factors and their effect on the success of the technique are discussed. In addition, future developments for the integration of the traditional Masquelet Technique with the use of alternative biomaterials to increase the effectiveness and expand the clinical applicability of the Masquelet Technique are reviewed. Abstract : The Masquelet technique is a two‐step surgical procedure used to treat critical‐sized bone defects. Although clinically effective, the physiology of healing is not well understood and much has yet to be elucidated and optimized. Multiple modifiable factors have been identified and implemented. This review looks at the factors crucial to the success of the Masquelet technique and how we can further optimize them in clinical practice.